Bactericidal efficacy of molybdenum oxide nanoparticles against antimicrobial‐resistant pathogens. Issue 8 (August 2018) - Lopes, E.; Piçarra, S.; Almeida, P. L.; de Lencastre, H.; Aires‐de‐Sousa, M.
Abstract : N/A: Multidrug‐resistant bacteria pose a major threat to effective antibiotics and alternatives to fight multidrug‐resistant pathogens are needed. We synthetized molybdenum oxide (MoO3 ) nanoparticles (NP) and determined their antibacterial activity against 39 isolates: (i) eight Staphylococcus aureus, including representatives of methicillin‐resistant S. aureus epidemic clones; (ii) six enterococci, including vancomycin‐resistant isolates; and (iii) 25 Gram‐negative isolates ( Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Acinetobacter baumannii, Enterobacter cloacae ), including extended spectrum beta‐lactamases and carbapenemases producers. All isolates showed a MoO3 NP MIC of 700–800 mg l −1 . MoO3 NP produced a clear inhibition zone for S. aureus and all Gram‐negative isolates at concentrations ≥25 mg ml −1 and ≥50 mg ml −1 for enterococci. When the NP solutions were adjusted to pH ˜7, the biocidal activity was completely abolished. MoO3 NP create an acidic pH and show a universal antimicrobial activity against susceptible and resistant isolates belonging to the most relevant bacterial species responsible for hospital‐acquired infections.